Efek Sabar dan Syukur Terhadap Penyesuaian Pernikahan - Zuliana, Nafira; Kumala, Anisia (TAZKIYA Journal of Psychology, 2020)
One of the keys to achieving a quality of marriage is the marital adjustment. Marital adjustment is defined as the process of mutual adjustment between husband and wife in all aspects of their life. There are many challenges faced, so it requires patience and gratitude. Patience is self-control from bad actions, accompanied by an optimistic attitude, never giving up, being open to new information and solutions, and not easily complaining. Meanwhile, gratitude can be defined as positive feelings to oneself, others, the environment and even God, and is expressed in behavior. This study aimed to explore effect of patience and gratitude on marital adjustment. The research approach used is quantitative, involving 203 respondents (male = 64, female = 139), taken by purposive sampling technique. Criteria of respondent are married Muslim, age of marriage between 0-2 years. The scale used in this study is the RDAS (Revision Dyadic Adjustment Scale) for marital adjustments with 0.796 reliability, the Patience Scale with 0.749 reliability and the Gratitude Scale in Islamic Psychology with a reliability of 0.839. Statistical analysis techniques use multiple regression. The results of this study indicate an F value of 18,717 with a probability value of 0.000 (p <0.05). This data shows that the variables of patience and gratitude have an effect on marital adjustments by 15.8 percent, or with the R square coefficient (R²) value of 0.158.